2008
DOI: 10.1144/sp308.7
|View full text |Cite
|
Sign up to set email alerts
|

Pre-metamorphic carbon, oxygen and strontium isotope signature of high-grade marbles from the Lützow-Holm Complex, East Antarctica: apparent age constraints of carbonate deposition

Abstract: C, O and Sr isotope geochemistry of high-grade marbles from the Lützow-Holm Complex, East Antarctica, has given clues on the depositional ages and post-depositional alterations. Dolomitic and calcitic marbles occur as thin layers with varying thickness (up to 100 m) in several outcrops in eastern Dronning Maud Land, most of which underwent postdepositional geochemical alterations. In particular, the Sr and O isotope alterations are extensive, with 87 Sr/ 86 Sr (550 Ma) ratios as high as 0.758 and d 18 O values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 56 publications
2
9
0
Order By: Relevance
“…Katz (1971) suggested that the repeated layer‐wise occurrence of silimanite‐bearing garnet biotite gneiss, quartzite, and marble in the HC of Sri Lanka represents the shale, sandstone, and limestone, respectively. Similar meta‐sedimentary sequences are widespread elsewhere in the world and have been identified in the KKB in India (Pradeepkumar & Krishnanath, 1996; Satish‐Kumar & Niimi, 1998; Satish‐Kumar, Wada, Santosh, & Yoshida, 2001; Wang, Zhang, Dai, & Lan, 2015) and the LHB in Antarctica (Satish‐Kumar et al, 2008; Tsunogae, Yang, & Santosh, 2015) as well. The common occurrence of oligomictic rock fragments in the investigated marbles have been interpreted as sills that have been boudinaged under high‐shear stress due to their greater competency than marbles (Kehelpannala, 1997).…”
Section: Discussionsupporting
confidence: 63%
“…Katz (1971) suggested that the repeated layer‐wise occurrence of silimanite‐bearing garnet biotite gneiss, quartzite, and marble in the HC of Sri Lanka represents the shale, sandstone, and limestone, respectively. Similar meta‐sedimentary sequences are widespread elsewhere in the world and have been identified in the KKB in India (Pradeepkumar & Krishnanath, 1996; Satish‐Kumar & Niimi, 1998; Satish‐Kumar, Wada, Santosh, & Yoshida, 2001; Wang, Zhang, Dai, & Lan, 2015) and the LHB in Antarctica (Satish‐Kumar et al, 2008; Tsunogae, Yang, & Santosh, 2015) as well. The common occurrence of oligomictic rock fragments in the investigated marbles have been interpreted as sills that have been boudinaged under high‐shear stress due to their greater competency than marbles (Kehelpannala, 1997).…”
Section: Discussionsupporting
confidence: 63%
“…Whether external input of Cl is required to attaiñ 0.40 wt%Cl in biotite or not depends on initial Cl content in biotite and degree of partial melting that consumes biotite. However, in Skallen and Skallevikshalsen, Cl-rich scapolite in marbles has been considered as a result of hypersaline fluid that was present during scapolite formation (Satish-Kumar et al, 2006;2008b). Since Cl-rich scapolite is stable under the peak P-T condition (>1.2 GPa, 820-850°C) of Skallevikshalsen (e.g., Filiberto et al, 2014), infiltration of brine during prograde to peak metamorphic stage is highly likely (e.g., Satish-Kumar et al, 2008b).…”
Section: Formation Mechanism Of Cl-enriched Biotite Included In Garnetmentioning
confidence: 99%
“…However, in Skallen and Skallevikshalsen, Cl-rich scapolite in marbles has been considered as a result of hypersaline fluid that was present during scapolite formation (Satish-Kumar et al, 2006;2008b). Since Cl-rich scapolite is stable under the peak P-T condition (>1.2 GPa, 820-850°C) of Skallevikshalsen (e.g., Filiberto et al, 2014), infiltration of brine during prograde to peak metamorphic stage is highly likely (e.g., Satish-Kumar et al, 2008b). Therefore, brine infiltration into the pelitic lithology, followed by the partial melting process discussed above, is one of the possible processes to have elevated the Cl content in biotite in the studied sample.…”
Section: Formation Mechanism Of Cl-enriched Biotite Included In Garnetmentioning
confidence: 99%
“…These metacarbonates have been considered as traces of the subducted and exhumed oceanic carbonates derived from the Mozambique Ocean floor, which were incorporated into the accretionary belt (Santosh et al, 2009a). Satish-Kumar et al (2008) reported the 87 Sr/ 86 Sr isotopic ratios and apparent depositional ages of ca. 730-830 Ma for high-grade marbles from the Lützow-Holm Complex in East Antarctica along the extension of the Gondwana suture.…”
Section: Discussionmentioning
confidence: 99%